2009
DOI: 10.1007/s11099-009-0009-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of susceptivity to photoinhibition and photooxidation in rice chlorophyll b-less mutants

Abstract: Two rice chlorophyll (Chl) b-less mutants (VG28-1, VG30-5) and the respective wild type (WT) plant (cv. Zhonghua No. 11) were analyzed for the changes in Chl fluorescence parameters, xanthophyll cycle pool, and its de-epoxidation state under exposure to strong irradiance, SI (1 700 μmol m −2 s −1 ). We also examined alterations in the chloroplast ultrastructure of the mutants induced by methyl viologen (MV) photooxidation. During HI (0−3.5 h), the photoinactivation of photosystem 2 (PS2) appeared earlier and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…A. acuminatissima as a mesophytes species had a large-scale feasible growing light intensities with a significant decrease of RLC after growing with overshadow treatment. The amount of acceptors or donors nearby P 680 of tested plant was supposed to be reduced and resulted in lessening the function of PSII in accepting light energy and transferring electron (Demmig-Adams and Adams 1992; Lin et al 2009). When treated by NaHSO 3 , relative electron transport rate of PSII (ETR) and actual photochemical efficiency of PS II (DF/Fm 0 ) were extremely affected in P. massoniana needles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A. acuminatissima as a mesophytes species had a large-scale feasible growing light intensities with a significant decrease of RLC after growing with overshadow treatment. The amount of acceptors or donors nearby P 680 of tested plant was supposed to be reduced and resulted in lessening the function of PSII in accepting light energy and transferring electron (Demmig-Adams and Adams 1992; Lin et al 2009). When treated by NaHSO 3 , relative electron transport rate of PSII (ETR) and actual photochemical efficiency of PS II (DF/Fm 0 ) were extremely affected in P. massoniana needles.…”
Section: Discussionmentioning
confidence: 99%
“…As to the thylakoid membrane organization and function, light has long been considered as the most important modifying factor (González et al 1993;Moharekar et al 2007). Growing with different light exposures determined the electron transport ability of chloroplast, the stacking density and grana size in thylakoid (Anderson 1986;Lin et al 2009). Here, Grown under 12% natural light resulted in a more compact thylakoid stacking structure in three species for providing more light harvesting complexes in PSII in order to effectively utilize the limited light energy.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 The connection between mature and young leaves (net exporters and importers of biosynthesized nutrients, respectively) is usually called source-to-sink relationship and occurs through the phloem. [2][3][4][5][6][7][8] When young leaves import amino acids and ureides from the roots, the connection is usually called root-to-shoot transportation and occurs via the xylem. 3 Studies on the synthesis, mobility and storage of metabolites within plants have been conducted for decades.…”
Section: Introductionmentioning
confidence: 99%
“…, Lin et al. ). In this study, the lcb1 mutant showed a significantly decreased chlorophyll b content and a Chl a/b ratio of almost 10; therefore, it is a low chlorophyll b mutant (Terao et al.…”
Section: Discussionmentioning
confidence: 99%